Neighborhood Effects in Integrated Social Policies. (8th November 2016) - Bobba, Matteo; Gignoux, Jérémie
Abstract: When potential beneficiaries share their knowledge and attitudes about a policy intervention, their decision to participate and the effectiveness of both the policy and its evaluation may be influenced. This matters most notably in integrated social policies with several components. We examine spillover effects on take-up behaviors in the context of a conditional cash transfer program in rural Mexico. We exploit exogenous variations in the local frequency of beneficiaries generated by the program's randomized evaluation. A higher treatment density in the areas surrounding the evaluation villages increases the take-up of scholarships and enrollment at the lower-secondary level. These cross-village spillovers operate exclusively within households receiving another component of the program, and do not carry over larger distances. While several tests reject heterogeneities in impact due to spatial variations in program implementation, we find evidence to suggest that spillovers stem partly from the sharing of information about the program among eligible households.